Latest advances and prospects in the pathogenesis, animal models, and vaccine research of severe fever with thrombocytopenia syndrome virus - Chen, Chenghao; Li, Jiaxuan; Zhou, Yumo; Zhang, Yuwen; Huang, Renjin; Zhang, Yanjun; Li, Jianhua; Chen, Keda (Frontiers in Immunology, 2025)
Severe Fever with Thrombocytopenia Syndrome Virus (SFTSV), a tick-borne phlebovirus first identified in China, causes severe illness characterized by high fever, thrombocytopenia, leukopenia, and, in some cases, multi-organ failure and death. With mortality rates ranging from 5% to 30% in endemic regions, SFTSV has emerged as a significant public health threat across East Asia, including South Korea and Japan, with potential for broader outbreaks. This review synthesizes recent advances in SFTSV animal models and candidate vaccines, highlighting their contributions and limitations. Current animal models, including mice, ferrets, and non-human primates, partially replicate human disease but fail to fully recapitulate clinical manifestations, limiting their translational utility. Vaccine development has shown promise, with candidates such as mRNA, subunit, and viral vector vaccines demonstrating efficacy in preclinical studies, yet none have progressed to clinical trials. Key challenges include viral genetic diversity and immune evasion. Future research should focus on refining animal models to better mimic human pathology, developing broad-spectrum vaccines, and integrating virological and immunological insights to enhance prevention and treatment strategies for SFTSV.